2018
DOI: 10.1111/jfd.12832
|View full text |Cite
|
Sign up to set email alerts
|

In vivo virulence and genomic comparison of infectious Salmon Anaemia Virus isolates from Atlantic Canada

Abstract: The infectious salmon anaemia virus (ISAV) is capable of causing a significant disease in Atlantic salmon, which has resulted in considerable financial losses for salmon farmers around the world. Since the first detection of ISAV in Canada in 1996, it has been a high priority for aquatic animal health management and surveillance programmes have led to the identification of many genetically distinct ISAV isolates of variable virulence. In this study, we evaluated the virulence of three ISAV isolates detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…On S5, a prerequisite of virulence seems to be a Q 266 →L 266 substitution or Q 266 with an insertion close to the putative cleavage site (Devold, 2006 ; Markussen et al., 2008 ). Association of these markers to virulent variants of ISAV has been supported over the years (Cárdenas et al., 2019 ; LeBlanc et al., 2018 ). This is the first report of the successful isolation in cell culture, supported with data, of a natural HPR0 variant, as defined by current genotyping, but is also the first report of a natural ISAV variant possessing a S6 typical of non‐virulent variants (no deletion in the HPR) and a S5 typical of virulent variants (Q 266 with an insertion).…”
mentioning
confidence: 95%
“…On S5, a prerequisite of virulence seems to be a Q 266 →L 266 substitution or Q 266 with an insertion close to the putative cleavage site (Devold, 2006 ; Markussen et al., 2008 ). Association of these markers to virulent variants of ISAV has been supported over the years (Cárdenas et al., 2019 ; LeBlanc et al., 2018 ). This is the first report of the successful isolation in cell culture, supported with data, of a natural HPR0 variant, as defined by current genotyping, but is also the first report of a natural ISAV variant possessing a S6 typical of non‐virulent variants (no deletion in the HPR) and a S5 typical of virulent variants (Q 266 with an insertion).…”
mentioning
confidence: 95%
“…Table 1). 30 Reference segment coverage of assembled contigs ranged from 65.0–102% because some of the assembled contigs were longer than the reference accession lengths and some shorter as a result of markedly lower coverage on both platforms across the shortest ISAV segment. To elucidate whole-genome comparison between our draft genome and publicly available whole ISAV genomes, we mapped the data to GenBank KX424582–KX424589 and found that raw reads aligned to these 8 segments with high concordance, yielding a consensus genome with ≥ 14 high-quality SNVs—5 of which confer amino acid substitutions—with GridION sequencing depth > 100× and/or MiSeq depth > 50× (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Segment six houses a highly polymorphic region (HPR) which is commonly used for genotyping (Aamelfot, Dale, & Falk, ; Cunningham, Gregory, Black, Simpson, & Raynard, ; Fourrier et al., ; Mjaaland et al., ; Ritchie et al., ). It is accepted that the HPR genotype is at least partially responsible for ISAV strain virulence, although other virulence‐related factors have also been suggested (Kibenge et al., ; LeBlanc, Leadbeater, Laflamme, & Gagne, ; Markussen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…virulence, although other virulence-related factors have also been suggested (Kibenge et al, 2007;LeBlanc, Leadbeater, Laflamme, & Gagne, 2018;Markussen et al, 2008).…”
mentioning
confidence: 99%